2019
DOI: 10.1186/s12955-019-1147-4
|View full text |Cite
|
Sign up to set email alerts
|

Usability of daily SF36 questionnaires to capture the QALD variation experienced after vaccination with AS03A-adjuvanted monovalent influenza A (H5N1) vaccine in a safety and tolerability study

Abstract: Background This study aims to describe the short-term reactogenicity of the AS03-adjuvanted H5N1 vaccine expressed through adverse events (AEs) and quality-adjusted life-day (QALD) scores. The AEs are likely to be short-term and therefore the quality of life (QoL) questionnaire, SF-36v2, was administered daily to record changes over seven days. A more sensitive application of this instrument should allow for a better understanding of short-term tolerability of adjuvanted vaccines. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The higher QALY loss post-dose 2 versus post-dose 1 is consistent with the incidence of Grade 3 reactogenicity after the first and second doses in this study. In comparison with the results presented here, a recent study reported that reactogenicity after an adjuvanted monovalent influenza A vaccine resulted in a QALY loss of 0.00011 ( 20 ), similar to that observed in the present study. By contrast, it has been previously reported that QALY losses due to HZ, including postherpetic neuralgia (PHN), ranged from 0.021 to 0.22 ( 21 , 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…The higher QALY loss post-dose 2 versus post-dose 1 is consistent with the incidence of Grade 3 reactogenicity after the first and second doses in this study. In comparison with the results presented here, a recent study reported that reactogenicity after an adjuvanted monovalent influenza A vaccine resulted in a QALY loss of 0.00011 ( 20 ), similar to that observed in the present study. By contrast, it has been previously reported that QALY losses due to HZ, including postherpetic neuralgia (PHN), ranged from 0.021 to 0.22 ( 21 , 22 ).…”
Section: Discussionsupporting
confidence: 92%
“… [12] A study of adjuvanted flu vaccine in older adults also showed the impact of adverse events on daily life measured with a quality of life score. [17] Another important issue is the effect of reactogenicity on household economy, one fifth of wP-group parents incurred extra expenses and around one third reported job absenteeism, contributing to productivity and income losses in vulnerable populations. These data can be useful for future pharmacoeconomic studies in Argentina and also in Latin America, since similar wP-pentavalent vaccines are provided by the PAHO Revolving Fund in the region.…”
Section: Discussionmentioning
confidence: 99%
“…33 These delayed outcomes are hard to assign to the first or the second dose. Therefore, given the explorative nature of this study, the QALY loss as a result of vaccination was included by proxy, as we applied a QALY loss measured in the first 21 days of an adjuvanted H5N1 vaccine, 34 which observed a QALY loss of 0.00011 QALYs per administered vaccine. As a secondary analysis we estimated our own side effect: a QALY loss of being for one day in EQ5D state 11121 (ie, perfect health but with moderate pain), which would be the equivalent of 0.00045 QALYs lost per dose.…”
Section: Quantification Of Direct Effects Herd Effect and Side Effectsmentioning
confidence: 99%